Behavior of Reinforced Concrete Composite Beams with Embedded Prestressed Concrete Prisms Using Nonlinear Finite Element Analysis - Al-Hadithy, Laith Khalid; Abdal-Kareem, Hamza Sadiq (Nahrain University College of Engineering Journal, 2008)
The investigation described herein deals with a theoretical study of the flexural behavior of simply supported composite beams consisting of precast prestressed concrete prisms as tension reinforcement in reinforced concrete, by developing a non-linear three-dimensional finite element model. Eight-node isoparametric brick elements with and without smeared steel reinforcement are used to model the reinforced concrete medium and the precast concrete prismrespectively, using the corresponding material properties and considering the appropriate tensile cracking and compressive crushing phenomena for each , while a two-node threedimensional axial element capable of plastic post-yield deformation is used for modeling the prestressing steel strands. Perfect bond isassumed for all concrete-concrete and steelconcrete contact surfaces. with its qualified brick and axial elements is used to predict the load-deflection behavior offour typical simply supported beams using such composite system and varying in crosssectional whole dimensions and areas of precast prisms, prestressing strands and nonprestressed rebars. That behavior is compared with behavior of four previously tested corresponding specimens to verify the accuracy of the finite element model in the linear and post-cracking stages. A parametric study comprizing effects of the relative eccentricity of the prestressingstrands and the geometric state of precast prestressed prisms on flexural behavior of this composite system is preformed to compute these effects on stiffness and ultimate resistance proving their major role after cracking which depends on the relative quantities of precast prisms and prestressing strands.Accurate results of the present finite element model has proved its effectiveness and reliability in the analysis of such composite systems, hence giving motive to widen its application in that field